'Even if they ask you to stand by a tree all day, you will have to do it (laughter)...!': community voices on the notion and practice of informed consent for biomedical research in developing countries. - Molyneux, C; Wassenaar, DR; Peshu, N; Marsh, K (2005)
Ethical dilemmas in biomedical research, especially in vulnerable populations, often spark heated debate. Despite recommendations and guidelines, many issues remain controversial, including the relevance, prioritisation and application of individual voluntary informed consent in non-Western settings. The voices of the people likely to be the subjects of research have been notably absent from the debate. We held discussions with groups of community members living in the rural study area of a large research unit in Kenya. Discussions were facilitated by three research study vignettes outlining one field-based and two hospital-based studies being planned or taking place at the time. In addition to gathering general views about the aims and activities of the research unit, questions focused on whether consent should be sought for studies, and if so from whom (chiefs, elders, men/women, children), and on ascertaining whether there are any special concerns about the physical act of signing consent forms. The findings revealed the community's difficulty in distinguishing research from clinical investigations conducted in clinical settings. There was a spectrum of views regarding perceived appropriateness of consent procedures, in part because of difficulty in disentangling clinical from research aims, and because of other challenges to applying consent in practice. Debates between community members highlight the inadequacy of simplistic assumptions about community members' views on informed consent, and the complexity of incorporating lay opinions into biomedical research. Failure to appreciate these issues risks exaggerating differences between settings, and underestimating the time and resources required to ensure meaningful community involvement in research processes. Ultimately, it risks inadequately responding to the needs and values of those on whom the success of most biomedical research depends. Although compliance with community views does not necessarily make the research more ethical, it is argued that community opinions on local issues and practices should inform ethical decision-making in health research.